Book Review: Gust Blauwens, Peter de Baere and Eddy Van de Voorde Transport Economics - Button, Kenneth (European Journal of Transport and Infrastructure Research, 2004)
Academic interest in transport economics waxes and wanes. It was initiated (at least in its modern form) in France in the 1840s and 1850s to handle issues of investment and pricing of transport infrastructure. The advent of the railways raised challenges of monopoly power, regulation and, in some countries, appropriate ownership. The internal combustion engine brought with it initially economic questions associated with traffic congestion and more recently concerns with environmental degradation. Regulation issues returned to the forefront from the 1980s as new approaches to economic regulation emerged and as there was increased interest in making fuller use of market instruments. Overlapping this, the globalization of trade and the formation of trade blocks such as the European Union has led to a more detailed look at the role transportation plays in the economic development process.